The Influence of Product Diversity, Store Atmosphere, and Service Quality on Customer Satisfaction at Sports Station Galaxy Mall Surabaya - Faradilla Aghnia Alifia; Lia NIrawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rapid development of the retail business in Indonesia is closely linked to shifts in consumer shopping behavior. One of the retail brands actively competing in this dynamic environment is Sports Station, which specializes in the sale of various sports-related products. This study aims to examine the influence of product diversity, store atmosphere, and service quality on customer satisfaction at Sports Station Galaxy Mall Surabaya. This research adopts a quantitative approach with an associative research design. Data were collected through the distribution of questionnaires to selected respondents, and statistical processing was conducted using SPSS version 18. The primary analytical method employed in this study is multiple linear regression analysis. The results of the study reveal that product diversity, store atmosphere, and service quality have a simultaneous and statistically significant influence on customer satisfaction. Furthermore, the partial (t-test) results indicate that each of the independent variables—product diversity, store atmosphere, and service quality—also has a significant individual effect on customer satisfaction at Sports Station Galaxy Mall Surabaya.